Effects of Dynamic Characteristics on 5-Storey Steel Tower with Different Structural Configurations Title - Masri, Badrun Amin; Kamarudin, Ts. Dr. Ahmad Fahmy (Recent Trends in Civil Engineering and Built Environment, 2022)
This paper was determined the effect of dynamic characteristics on 5-storey steel tower with different structural configurations by using modal analysis through STAAD Pro software. There are two types of structural configurations found in the structure which is cross-section and connection. Dynamic characteristics of steel tower was investigated in terms of predominant frequency, maximum deflection amplitude and relative floor displacement amplitude. In this study was focused to verified the comparison result from bare frame with the previous laboratory measurement. There are three predominant frequency was produced from modal analysis which according to their modes. The result of bare frame is f1 and f2 = 5.55Hz, and f3 = 7.23Hz with percentage different less than 10% from previous study. Besides, there are three type of modes shapes for steel tower which can be explained in translational mode and torsional mode. The translational mode was produced for mode 1 and mode 2 while torsional mode for mode 3. The relationship of predominant frequency, maximum deflection amplitude and relative floor displacement were developed between the dynamic characteristics of steel tower. Result has been proved the maximum deflection for all cases in two types of structural configurations were located at top level of steel tower. While, the maximum displacement amplitude for weak storey were located on the level 2 and level 3 which need an improvement to be done for maintaining the structure.